The Role of Agropolitan Project in Eradicating Poverty: Multidimensional Poverty Index - Ismail, Mohd Khairi; Siwar, Chamhuri; Alam, A. S. A. Ferdous; Ghazali, Rospidah; Talib, Basri Abdul (International Journal of Engineering and Technology, 2018)
Objective: This study aims to measure the poverty rate of the participants of the Agropolitan Projects by using the Multidimensional Poverty Index (MPI).Methodology: The measurement of MPI used 14 indicators, which covered the dimensions of education, health, living standards, household income, mindset, and environment. This study measured the poverty rate of smallholders within the same area by comparing the poverty levels between the participants and non-participants of this project. This comparison was done as a foundation to expound the effectiveness of Agropolitan Projects in eradicating poverty. The number of samples for the study consisted of 45 participants from the Gahai Agropolitan Project, Lipis and 45 rubber smallholders in Lipis, Pahang, Malaysia.Results:  The findings showed that all household members of the participants from the Gahai Agropolitan Project, Lipis were free from multidimensional poverty. The MPI also shows that 2.91% of household members of rubber smallholders in Lipis were categorised as multidimensional poor. This study proved that the Gahai Agropolitan Project was able to eradicate multidimensional poverty among the participants within the project.Implication: MPI is a comprehensive method in measuring the poverty level, which can help the policymakers to outline an effective poverty eradication programme based on the perspective of multidimensional poverty index.